Impaction of swallowed dentures in the sigmoid colon requiring sigmoid colectomy. (2018) - Flanagan, Michael; Clancy, Cillian; O Riordain, Micheal G.
Highlights: Patient who underwent sigmoid colectomy and end-to-end anastomosis following delayed presentation of dental plate ingestion. Delayed presentation resulted in an unusual disease process of thickened colon with local inflammatory response. Foreign body ingestion may present a diagnostic challenge requiring multiple imaging and endoscopic modalities. Indications for resection include chronicity of the ingested FB, extend of localised or diffuse peritonitis, and area of bowel involved. Abstract: Introduction: Foreign body (FB) ingestion results in perforation in 1% of cases and is associated with significant morbidity and rarely mortality. Clinical presentation is variable and can present a diagnostic challenge. We report our experience and management of a patient with a delayed presentation of a sigmoid colon foreign body as a result of ingestion of a dental plate. Presentation of case: A 67 year old female attended the colorectal outpatient clinic following an incidental finding of a sigmoid mass on computed tomography (CT) abdomen. Further investigation identified a dental plate impacted in a thickened sigmoid colon. On further questioning the patient recalled losing her dentures three years previously. At surgery the dental plate had partially eroded through the sigmoid colon into the pelvic side wall. A sigmoid colectomy and hand sewn end-to-end colo-colic anastomosis was performed. Discussion: Localised perforation following ingestion of a foreign body may result in significant morbidity. Extra luminal migration and local inflammatory response resulted in the formation of a walled off collection. Delayed complications of perforation include abscess and fistula formation. Conclusion: Clinicians need to exhibit a high index of suspicion when treating edentulous patients and alcohol and drug abusers who present with an acute abdomen or a sub-acute presentation with associated atypical imaging and endoscopic findings. The decision regarding intervention and management strategy in cases of perforation by foreign body depends on chronicity of the case, extent of localised or diffuse peritonitis, and size of the lesion or area of bowel involved.